Integrated waste management based on sustainable approaches, methods and systems in Sinjai regency - Falah, Fahsul; Jamil, Muhammad Hatta; Demmallino, Eymal B; Arsal, Ariady; Darmawansyah, Darmawansyah; Darhamsyah, Darhamsyah; Massiseng, Andi Nur Apung (Edelweiss Applied Science and Technology, 2025)
Waste management in Sinjai Regency aligns with Regional Regulation Number 28 of 2018 concerning Policies and Strategies for the Management of Household Waste and Waste Similar to Household Waste. This study aims to analyze the methods, management systems, and recycling efforts in Sinjai Regency, as well as their implications for ecosystem sustainability. The research used a descriptive qualitative and quantitative approach with analysis based on normative standards. A case study method was applied using Delphi analysis, content analysis, and SERVQUAL (Importance Performance Analysis). Sampling was conducted through Stratified Random Sampling. The Delphi analysis results indicate that the waste management system is influenced by service quality, waste removal processes, transportation to landfills, and operational procedures. Meanwhile, analysis based on the Indonesian National Standard (SNI) shows that these standards are important references for ensuring effective waste collection. SERVQUAL analysis further reveals that community satisfaction depends heavily on the punctuality of waste collection according to the promised schedule. Overall, this research confirms that an effective and standardized waste management system plays a significant role in reducing environmental pollution, improving environmental quality, and maintaining ecosystem sustainability.